2017
DOI: 10.7150/thno.16236
|View full text |Cite
|
Sign up to set email alerts
|

Mouse IP-10 Gene Delivered by Folate-modified Chitosan Nanoparticles and Dendritic/tumor Cells Fusion Vaccine Effectively Inhibit the Growth of Hepatocellular Carcinoma in Mice

Abstract: Dendritic cells (DC) and tumor cell fusion vaccine (DC/tumor cell fusion vaccine) is considered an effective approach in cancer biotherapy. However, its therapeutic effects in early clinical trials have been suboptimal partially due to the immunosuppressive tumor environment. In this study, we used nanoparticles of folate (FA)-modified chitosan, a non-viral vector capable of targeting tumor cells with high expression of FA receptors. FA-chitosan nanoparticles were used as biological carriers for the expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(33 citation statements)
references
References 32 publications
(41 reference statements)
0
29
0
1
Order By: Relevance
“…In a murine trial of myeloma with administration of a CXCL10-Ig fusion protein, not only an enhancement of antitumor immunity but also a suppression of tumor growth was described (Barash et al 2014). In another study, the combination of CXCL10-loaded nanoparticles and DC/tumor cell fusion vaccine against hepatocellular carcinoma (HCC) effectively inhibited tumor cell proliferation in mice (Hu et al 2017). As CXCL9and CXCL10-mediated tumor infiltration by T-cells is suppressed due to DNA-methylation of the encoding genes, treatment with epigenetic modulating drugs can increase chemokine release and subsequently also effector T cell tumor-infiltration (Peng et al 2015).…”
Section: Role Of Chemokines In Tumor Immunology and In Immunotherapymentioning
confidence: 99%
“…In a murine trial of myeloma with administration of a CXCL10-Ig fusion protein, not only an enhancement of antitumor immunity but also a suppression of tumor growth was described (Barash et al 2014). In another study, the combination of CXCL10-loaded nanoparticles and DC/tumor cell fusion vaccine against hepatocellular carcinoma (HCC) effectively inhibited tumor cell proliferation in mice (Hu et al 2017). As CXCL9and CXCL10-mediated tumor infiltration by T-cells is suppressed due to DNA-methylation of the encoding genes, treatment with epigenetic modulating drugs can increase chemokine release and subsequently also effector T cell tumor-infiltration (Peng et al 2015).…”
Section: Role Of Chemokines In Tumor Immunology and In Immunotherapymentioning
confidence: 99%
“…Norcantharidin could induce apoptosis and inhibit proliferation of Tregs and its mechanism is probably associated with Vaccine therapy is an important and effective approach in treating many malignancies. 19,20 Several published studies have shown that GM-CSF-modified cell vaccines could induce effective antitumor immunity. 19,21 Granulocyte macrophage colony-stimulating factor plays a major role in maturation of DCs and activation of CD4 + and CD8 + T cells.…”
Section: Discussionmentioning
confidence: 99%
“…pH-sensitive microneedle chemically coated with inactivated polio vaccine and N-trimethyl chitosan chloride via electrostatic interactions for dermal vaccination in rats [127] Glycol chitosan nanoparticles for mucosal intranasal administration of hepatitis B vaccine [128] Folate-chitosan/ interferon-induced protein-10 gene nanoparticles and DC/tumor fusion vaccine enhanced anti-hepatocellular carcinoma effects in mice [129] Drug Delivery…”
Section: Tissue Engineeringmentioning
confidence: 99%